Artistic Skills Recovery and Compensation in Visual Artists after Stroke - Petcu, Eugen Bogdan; Sherwood, Katherine; Popa-Wagner, Aurel; Buga, Ana Maria; Aceti, Lanfranco; Miroiu, Rodica Ileana (Frontiers in Neurology, 2016)
Background Art is a characteristic of mankind, which requires superior central nervous processing and integration of motor functions with visual information. At the present time, a significant amount of information related to neurobiological basis of artistic creation has been derived from neuro-radiological cognitive studies, which have revealed that subsequent to tissue destruction, the artists continue to create art. The current study aims to review the most important cases of visual artists with stroke and to discuss artistic skills recovery and compensation as well as artistic style after stroke. Methods The role of various central nervous system regions in artistic creation was reviewed on the basis of previously published functional studies. Our PubMed search (1995–2015) has identified 10 famous artists with right cerebral stroke as well as 5 with left cerebral stroke who survived and continued to create art after stroke. As the artists included in this review lived at various times during the twentieth century and in different countries, clinical information related to their case was limited. However, it appears that artistic skills recovery and compensation appear within days after stroke. Some of the artists would subsequently change their artistic style. All these elements have been evaluated within the context of specific clinical cases. Conclusion The poststroke artistic skills recovery and compensation with development of a new style or the opposite, regaining the previous prestroke style, represents a significant element of clinical importance in medical rehabilitation as well as neuroesthetics, which requires further evaluation. At the present time, the molecular mechanisms of artistic creation are poorly understood, and more standardized clinical and experimental studies are needed.